The Role of Employee Commitment in Mediating the Influence of Transformational Leadership, Work Environment and Work Motivation on the Performance of Generation Z Human Resources - Syahrul Nursapni G; Asti Nur Aryanti; Gurawan Dayona; Nunung Ayu Sofiati; Ridlwan Muttaqin (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The purpose of this study is to examine how employee commitment functions as a mediator in the relationship between the performance of Generation Z HR at the Timiangan Raya Farmers Cooperative Garden and transformational leadership, work environment, and work motivation. SEM-PLS was utilized for analysis in this quantitative investigation with 55 respondents. All of the constructs demonstrated strong validity and reliability, according to the measurement test results (loading factor > 0.70; composite reliability 0.94–0.97). Idealized impact on transformational leadership, non-physical aspects on the workplace, the need for accomplishment on work motivation, and emotional commitment on the commitment variable were the characteristics that contributed the most. According to the structural test results, transformational leadership (β = 0.638; p = 0.005) and the work environment (β = 0.524; p < 0.001) were the strongest factors influencing HR performance, while the work environment was the most dominant variable influencing commitment (β = 0.958; p < 0.001). Although it had a smaller coefficient (β = –0.156; p = 0.015), work motivation also had an impact. The results of the mediation test indicated that while commitment did not mediate the impact of the work environment (p = 0.157), it did mediate the influence of transformational leadership (p = 0.016) and work motivation (p = 0.042) on HR performance. With an R2 value of HR performance = 0.953 and an R2 value of commitment = 0.945, the research model demonstrated exceptionally high predictive power. These results demonstrate that the quality of the work environment and leadership have the most effects on boosting the commitment of Generation Z employees. As a result, performance enhancement efforts should concentrate on fostering a positive work environment and motivating leadership.